2015
DOI: 10.1111/dme.13023
|View full text |Cite
|
Sign up to set email alerts
|

The association between sociodemographic and clinical characteristics and poor glycaemic control: a longitudinal cohort study

Abstract: Although our results may be limited by the observational nature of the study, the large geographically defined sample size, longitudinal design and robust definition of poor glycaemic control are important strengths. These findings demonstrate the complexity associated with poor glycaemic control and indicate a need for tailored interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
5
15
0
Order By: Relevance
“…Other studies of adults with T1DM have found that glycemic control tends to improve with increasing age. 17,2224 Episodes of severe hypoglycemia were more common among older people in the current study, a finding that has been reported previously. 17,22 DKA was less common with increasing age, which has also been reported previously.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies of adults with T1DM have found that glycemic control tends to improve with increasing age. 17,2224 Episodes of severe hypoglycemia were more common among older people in the current study, a finding that has been reported previously. 17,22 DKA was less common with increasing age, which has also been reported previously.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to studies conducted in the Arabian Gulf [ 49 , 50 ] and other countries [ 18 , 51 ] we found that younger age groups (≤60 years) were at higher risk of inadequate glycaemic control. Younger people are more likely to be affected by the change in lifestyle and less likely to be adherent to a management plan because of active occupational and social life [ 52 ].…”
Section: Discussionsupporting
confidence: 90%
“…In this population‐based study of individuals with diabetes, we found that lower income and lower age were associated with higher HbA 1c levels. This occurred despite the publicly funded healthcare system in Ontario that covers hospital and physician services for all residents, and corroborates previously published findings from Alberta . Disparities in glycaemic control across income groups were more pronounced for individuals aged <65 years, who are not eligible for universal drug insurance and who must often rely on private insurance or pay out‐of‐pocket for their prescription drugs.…”
Section: Discussionsupporting
confidence: 84%
“…However, these gradients are significantly diminished at age 65 years when residents gain access to prescription drug coverage. In a study examining predictors of sustained poor glycaemic control, socio‐economic gradients were attenuated in those aged ≥66 years . In the USA, the implementation of Medicare Part D drug coverage was associated with improvements in drug utilization and reductions in cost‐related non‐adherence and out‐of‐pocket costs in seniors, especially for those who previously had no drug insurance or had only limited benefits through Medigap .…”
Section: Discussionmentioning
confidence: 99%